2014
DOI: 10.1111/rda.12313
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Patterns in Bovine Oocytes with Different Meiotic Competence Related to Their in vitro Maturation

Abstract: This study was designed to specify chromatin and mitochondrial patterns in bovine oocytes with different meiotic competence in relation to maturation progress, resumption of meiosis, MII onset and completion of maturation. Oocytes with greater or lesser meiotic competence, recovered separately from medium (MF) and small follicles (SF), were categorized according to morphology. Four oocyte categories, healthy and light-atretic MF and healthy and light-atretic SF oocytes were matured and collected at 0, 3, 7, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Huang et al (19,20) reported that in vitro-grown oocytes acquired high mitochondrial activity after 10-h prematurational culture, and showed higher maturation and development competences compared to oocytes without prematurational culture. Jeseta et al (24) reported that the kinetics of mitochondrial activity and adenosine triphosphate (ATP) production during maturational culture were influenced by the atretic grade of granulosa cells. This indicates the importance of the correlation between oocyte and granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (19,20) reported that in vitro-grown oocytes acquired high mitochondrial activity after 10-h prematurational culture, and showed higher maturation and development competences compared to oocytes without prematurational culture. Jeseta et al (24) reported that the kinetics of mitochondrial activity and adenosine triphosphate (ATP) production during maturational culture were influenced by the atretic grade of granulosa cells. This indicates the importance of the correlation between oocyte and granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, after maturation, oocytes exhibit a large percentage of mitochondria with high activity [24]. Additionally, mitochondrial activity is especially high in oocytes with better morphological quality and competence, wherein changes in the distribution pattern (in particular, the aggregation pattern of mitochondria in the cytoplasm), and high ATP production are observed [27][28][29]. The association between increased mitochondrial activity and changes in their distribution can be described not only in cattle but also in other species (e.g., pig: [30]; horse: [31]).…”
Section: Oocytesmentioning
confidence: 99%
“…The availability of functional mitochondria is important for oocyte developmental competence [53], while mitochondrial clustering is conducive to ATP production. A high incidence of oocytes with mitochondrial granulations at the GV stage or mitochondrial clusters at MII stage has been associated with strong meiotic competence [37, 54]. When CXCR4 or SHP2 inhibitors were applied, many oocytes showed abnormal mitochondrial distribution and decreased mtDNA copy numbers (Figure 6A–C).…”
Section: Discussionmentioning
confidence: 99%